Production system and challenges of saline aquaculture in Punjab and Sindh provinces of Pakistan - Rossignoli, Cristiano M.; Obi, Chinedu; Ali, Syed Aman; Ullah, Najeeb; Khalid, Sidra; Hafeez, Mohsin; Shah, Syed Mehtab Hassan (Frontiers in Aquaculture, 2023)
This paper is based on one of the initial exploratory studies conducted on saline aquaculture systems in Pakistan, specifically focusing on Sindh and Punjab provinces. By delving into the current sectoral landscape, production challenges, post-harvest constraints, and capacity and investment needs, this study aims to bridge the knowledge gap and inform crucial policy decisions for the growth of saline aquaculture in the country.This investigation stems from an exploratory survey conducted in 2022 by the International Water Management Institute (IWMI) and WorldFish, focusing on the landscape of saline aquaculture in Pakistan. The survey specifically targeted Southern Punjab and Sindh Provinces, where soil salinity poses a growing challenge in the agriculture sector.According to FAO estimates (2022), aquaculture covers 121 thousand acres in Sindh and 27 thousand acres in Punjab, featuring fish farms averaging between 12 to 25 acres. Desk research indicates that in Punjab, 23% of the area contends with poor groundwater quality, while in Sindh, a substantial 78% of the groundwater is saline due to the confinement of fresh groundwater to a narrow strip along the river Indus (Qureshi, 2020). Annually, about 100 thousand acres are abandoned within the Indus Basin due to secondary salinization (Qureshi et al., 2008), rendering these areas unsuitable for traditional irrigation or field crop production.Recognizing the potential of saline areas in Punjab and Sindh for aquaculture, provincial fisheries departments introduced fish farming techniques in earthen ponds and community reservoirs as early as the 1960s. Patil et al. (2018) highlighted the introduction of polycultures involving Indian and Chinese carps in the two provinces since the 1980s. Recent trends reveal an increasing adoption of commercially produced fish feed, including floating and sinking pellets, by fish farmers.Punjab and Sindh were chosen for this study due to their significant potential for enhancing farmers livelihood through saline aquaculture.